2023
DOI: 10.3390/diagnostics13061107
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Chest X-ray Scores and their Relations with Clinical Variables and Outcomes in COVID-19 Patients

Abstract: Background: This study evaluated the temporal characteristics of lung chest X-ray (CXR) scores in COVID-19 patients during hospitalization and how they relate to other clinical variables and outcomes (alive or dead). Methods: This is a retrospective study of COVID-19 patients. CXR scores of disease severity were analyzed for: (i) survivors (N = 224) versus non-survivors (N = 28) in the general floor group, and (ii) survivors (N = 92) versus non-survivors (N = 56) in the invasive mechanical ventilation (IMV) gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
(58 reference statements)
0
4
0
Order By: Relevance
“…Ji et al (20) found that COVID-19 patients with comorbidities were more likely to progress to severe disease than those without comorbidities. Shen et al (60) found that mortality was significantly associated with comorbidities (e.g., hypertension, COPD, coronary artery disease, heart failure, and chronic kidney disease) in COVID-19 patients (p < 0.05). Some studies found that comorbidity at presentation was an independent high-risk factor for COVID-19 progression and mortality (20,61).…”
Section: Discussionmentioning
confidence: 99%
“…Ji et al (20) found that COVID-19 patients with comorbidities were more likely to progress to severe disease than those without comorbidities. Shen et al (60) found that mortality was significantly associated with comorbidities (e.g., hypertension, COPD, coronary artery disease, heart failure, and chronic kidney disease) in COVID-19 patients (p < 0.05). Some studies found that comorbidity at presentation was an independent high-risk factor for COVID-19 progression and mortality (20,61).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that initial chest X-ray scores of patients with COVID-19 are linked to clinical outcomes, such as mortality, the length of hospitalization and the duration of invasive ventilation ( 37 ). Since the beginning of the pandemic, comorbidities have been known to affect the outcomes of patients with COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, these features can be utilized as inputs in ML algorithms to develop predictive models for brain tumor diagnosis and treatment. Mathematically, it can be represented as: (10) The intensity value of each tumor region pixel is P(xi, yi). Calculate the tumor region's perimeter by measuring its boundary.…”
Section: B Feature Extraction and Selectionmentioning
confidence: 99%
“…Several ML methods, such as supervised learning, unsupervised learning, semi-supervised learning, and reinforcement learning, are used in the analysis of medical images. [10]. Each of these techniques is tailored to specific tasks, and their use in medical image analysis is expected to expand, leading to improved patient outcomes and reduced pressure on healthcare providers.…”
Section: Introductionmentioning
confidence: 99%